The implementation of forward chaining algorithm in calculating inheritance property based on faraid law / Nur Ain Syafiqah Mohammad Marzuki - Mohammad Marzuki, Nur Ain Syafiqah (2021)
Faraid is known as the Islamic Inheritance Law, which is a part of the Islamic Law that deals with the distribution of a deceased's properties among his or her heirs in accordance with what Allah S.W.T. defined in the Quran. Every Muslim should know how to manage the assets. However, the problems that occur to practice the Faraid among Muslim is the beneficiaries do not really understand the concept of Faraid that may lead to misunderstanding about Faraid distribution and have narrowed its application that will make it unworkable. Therefore, the purpose of this study is to facilitate the use of Forward Chaining Algorithm to calculate Faraid based on inheritance division. This study involves Muslim people and it is focusing on the calculation of the distribution of assets among eligible heirs through the use of Faraid law. The distribution of properties is solved using Python Programming Language and also will verify using Inheritance Calculator Mobile Application. The findings indicate that all rules that has been tested is similar with manual calculation and this shows that the algorithm is work and the objective has been achieved successfully.